Ekologi Tradisional Dayak Tamambaloh - Efriani Efriani; Jagad Aditya Dewantara; Dewi Utami; Indah Listyaningrum (Jurnal Ilmu Lingkungan, 2020)
Penduduk lokal khususnya yang tersebar di Nusantara memiliki beragam ekologi tradisional yang memiliki nilai-nilai konservatif. Di Kalimantan Barat, pada etnis Dayak Tamambaloh, terdapat fenomena pengelolaan lingkungan alam yang menjunjung nilai-nilai kelestarian. Mengkaji lebih dalam praktek ekologi tradisional Dayak Tamambaloh, menjadi tujuan utama penelitian ini. Data terkait praktek ekologi tradisional ini dikumpulan dengan wawancara mendalam, pengamatan lapangan dan studi dokumen. Tamanggung Tamambaloh, para petani, kelompok pengambil kebijakan dan pemangku adat Tamambaloh, ditentukan menjadi sumber informasi. Tindakan dalam pemanfaatan hutan dan isinya menjadi objek pengamatan. Beberapa buku terkait dengan profil ketamanggungan Tamambaloh, menjadi sumber informasi tertulis pada penelitian ini. Dari sejumlah data yang diperoleh di lapangan, ekologi tradisional Dayak Tamambaloh dapat dibagi dalam 4 kategori, yakni 1) pembagian kawasan adat berdasarkan peruntukannya, dan berdasarkan akses sumber daya, 2) Aturan akses sumber daya alam, 3) Proses pengambilan keputusan Pemanfaatan Sumber daya Alam, 4) Pengetahuan Gentika, dan 5) Kalender Musim. Kelima ekologi tradisional ini dapat direduksi ke dalam 4 model konservasi, yakni 1)Model Environmental Norms, 2) Model Proenvironmental Behavior  dan Environmental Concern, 3)Model Community Involvemen, dan 4) Model enviromental Dicision ABSTRACTThe Indigenous people, especially those scattered in the archipelago, has a variety of traditional ecologies that have conservative values. In West Kalimantan, the Dayak Tamambaloh ethnicity, there is a phenomenon of natural environmental management that upholds the importance of sustainability. Examining deeper into the traditional ecological practice of Dayak Tamambaloh is the main objective of this research. Data related to traditional ecological practices were collected through in-depth interviews, field observations and document studies. Tamanggung Tamambaloh, peasants, policy-making groups and Tamambaloh customary stakeholders were determined to be sources of information. Actions in forest utilization and their contents are objects of observation. Several books related to the Tamambaloh profile are the source of written information on this research. From a number of data obtained in the field, the traditional ecology of Dayak Tamambaloh can be divided into four categories, namely 1) division of common areas based on their designation and based on access to resources, 2) rules of access to natural resources, 3) Decision-making processes for the Use of Natural Resources, 4) scientific knowledge, and 5) seasonal calendars. These five traditional ecologies can be reduced to 4 conservation models, namely 1) Environmental Norms Model, 2) Proenvironmental Behavior and Environmental Concern Model, 3) Community Involvement Mode, and 4) Environmental Dicision Model.